0427 A cohort study of workers exposed to PFOA. (23rd June 2014) - Steenland, Kyle; Zhao, Liping; Winquist, Andrea
Abstract : Objectives: PFOA has been linked to several diseases, but findings are inconclusive, and there have been no incidence studies in worker populations. Method: We interviewed 3700 workers or their next-of-kin in 2009–2011 for medical history, and sought medical records to validate self-reported disease. A job-exposure matrix based on over 2000 PFOA serum measurements was used to estimate serum levels over time for each worker, while a separate estimation was made for non-occupational exposure due to drinking PFOA-contaminated water. Cumulative dose in the serum (ng/ml-years) was the metric of interest. We studied 18 disease outcomes with 15 to 1430 cases; analyses were limited to confirmed cases. Results: The median year of birth was 1951; 5% had died. The median measured serum level was 113 ng/ml in 2005 (n = 1900), compared to 4 ng/ml in the US population. Among 18 outcomes studied, only ulcerative colitis (10 year lag) showed a significant trend with increasing exposure (p = 0.05) (RRs by quartile 1.00, 3.00, 3.26, 6.57, p value trend 0.05), similar to earlier findings in a community cohort study in the same area. Positive but non-significant trends were also observed for prostate cancer and non-hepatitis liver disease, and female hypothyroidism, which have been implicated in other studies, No marked trends were seen for high cholesterol, which had been seen in the community study. Conclusions: Ulcerative colitis was linked to PFOA exposure among workers. Analyses of other diseases did not show marked trends. Data were limited by small numbers, a largely survivor cohort, and few low exposed referents.